Why do Women Invest? A Comparative Study of Women Stock and Non Stock Investors of Punjab - Kaur, Mandeep; Vohra, Tina (Gyan Management Journal, 2017)
Each investor has a unique investment objective. The objectives of investment vary across investors and are dependent upon a number of factors. Among several factors, one important factor that determines the choice of objective of investment among investors is the gender of an individual investor. Thus, the present study is an attempt to identify the investment objectives of women investors of Punjab and to explore if there are significant differences in the objective of making investments among women based on their demographics. For the purpose of the study, data were collected from primary sources using a pre tested, well structured questionnaire. Multi Response Analysis and Cross tabulation were used in order to analyze the collected data. The results of the study revealed that majority of women investors made investments with the objective of earning a high return and to ensure the safety of their funds. The paper suggests that since women with a higher personal monthly income invest in the stock market with an intention of saving tax, therefore it is proposed that women who intend to save tax should invest in Equity-linked saving schemes because of their tax-free status.
Keywords: Crosstabulation; Investing; Objectives; Multi Response Analysis; Women